Reduction of exposure to simulated respiratory aerosols using ventilation, physical distancing, and universal masking. (22nd February 2022) - Coyle, Jayme P.; Derk, Raymond C.; Lindsley, William G.; Boots, Theresa; Blachere, Francoise M.; Reynolds, Jeffrey S.; McKinney, Walter G.; Sinsel, Erik W.; Lemons, Angela R.; Beezhold, Donald H.; Noti, John D.
Abstract: To limit community spread of SARS‐CoV‐2, CDC recommends universal masking indoors, maintaining 1.8 m of physical distancing, adequate ventilation, and avoiding crowded indoor spaces. Several studies have examined the independent influence of each control strategy in mitigating transmission in isolation, yet controls are often implemented concomitantly within an indoor environment. To address the influence of physical distancing, universal masking, and ventilation on very fine respiratory droplets and aerosol particle exposure, a simulator that coughed and exhaled aerosols (the source) and a second breathing simulator (the recipient) were placed in an exposure chamber. When controlling for the other two mitigation strategies, universal masking with 3‐ply cotton masks reduced exposure to 0.3–3 µm coughed and exhaled aerosol particles by >77% compared to unmasked tests, whereas physical distancing (0.9 or 1.8 m) significantly changed exposure to cough but not exhaled aerosols. The effectiveness of ventilation depended upon the respiratory activity, that is, coughing or breathing, as well as the duration of exposure time. Our results demonstrate that a layered mitigation strategy approach of administrative and engineering controls can reduce personal inhalation exposure to potentially infectious very fine respiratory droplets and aerosol particles within an indoor environment.